Adjusting crystal morphology and emission behavior of organic fluorophore via the synergistic effect of proton and anion. (November 2021) - Ye, Guigui; Qu, Yinhe; Su, Lina; Li, Yingzhong; Chi, Baozhu; Wang, Hongming; Xia, Guomin
Abstract: We demonstrate here facile models, i.e. methyl 2-amino-4'-(pyridin-2-yl)-[1, 1′-biphenyl]-3-carboxylate (M) and its acidified counterpart (M − P), that trifluoroacetic acid (TFA) drives molecular rearrangement for synergistically adjusting crystal morphology and emission behavior. The pure M is able to self-organized into square microplates with bright blue emission, while turns out to be ordered microrods with intense yellow emission with the introduction of TFA. Structural analysis reveals that these differences between M and M−P crystals can be ascribed to their changed molecular packing modes from type of X-shaped hydrogen-bonds to antiparallel slight π-π stacking with low overlap area and weak interactions ( 3.5 Å), resulting from the protonated intrinsic pyridyl segments and concomitant trifluoroacetate anion. Graphical abstract: Image 1 Highlights: Facile microstructure models illuminate the synergistic effect of proton and anion on their property regulation. Trifluoroacetic acid drives molecular rearrangement for synergistically adjusting crystal morphology and emission behavior. Organic microcrystals exhibit tunable emission color from intense blue to yellow.